Early pulmonary fibrosis-like changes between delta and pre-delta periods in patients with severe COVID-19 pneumonia on mechanical ventilation - Jung-Wan Yoo; Won-Young Kim; Chi Ryang Chung; Young-Jae Cho; Jinwoo Lee; Yangjin Jegal; Junghyun Kim; Joon-Sung Joh; Tae Yun Park; Ae-Rin Baek; Joo Hun Park; Ganghee Chae; et al. (Scientific Reports)
Abstract It remains unclear whether pulmonary fibrosis-like changes differ in patients with different SARS-CoV-2 variants. This study aimed to compare pulmonary fibrotic changes between two SARS-CoV-2 variant periods (delta vs. pre-delta) in critically ill patients with SARS-CoV-2 pneumonia. Clinical data and chest CT images of patients with SARS-CoV-2 pneumonia receiving mechanical ventilation were collected from 10 hospitals in South Korea over two periods: delta (July-December, 2021; n = 64) and pre-delta (February, 2020-June, 2021; n = 120). Fibrotic changes on chest CT were evaluated through visual assessment. Of 184 patients, the mean age was 64.6 years, and 60.5% were ale. Fibrosis-like changes on chest CT (median 51 days from enrollment to follow up CT scan, interquartile range 27–76 days) were identified in 75.3%. Delta group showed more fibrosis-like changes (≥ 2) (69.8% vs. 43.1%, P = 0.001) and more frequent reticulation and architectural distortion+/-parenchymal band than pre-delta group. Even after propensity score matching with clinical variables, delta group had more severe (≥ 2) fibrosis-like changes (71.4% vs. 38.8%, P = 0.001), and more frequent reticulation and architectural distortion+/-parenchymal band than pre-delta group. Our data suggest that critically ill patients with SARS-CoV-2 in delta period had more severe pulmonary fibrosis-like changes than those in pre-delta period.